Pengaruh Motivasi Belajar, Fasilitas Belajar dan Kedisiplinan Belajar Terhadap Prestasi Belajar MIPA di SMA Negeri 1 Karangdowo - Sutaya Sutaya (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2020)
Objectives Specifically, this study has the following objectives. (1) To find out theinfluence of learning facilities at home on the learning achievement of Mathematics and Natural Sciences in Karangdowo 1 High School students. (2) To find out the effect of learning motivation on Mathematics and Natural Sciences learning achievement in students at Karangdowo 1 High School. (3) To determine the effect of learning discipline on the learning achievement of Mathematics and Natural Sciences in Karangdowo 1 High School students.The results showed, (1) There was a joint effect between learning facilities at home, MIPA learning motivation and joint learning discipline influenced the MIPA learning achievement of XIP MIPA students in SMA Negeri 1 Karangdowo Klaten Regency, so that the research hypothesis was accepted . (2) Learning facilities at home have a positive and significant effect on the learning achievement of Mathematics and Natural Sciences students of class XI MIPA in SMA Negeri 1 Karangdowo, Klaten Regency. (3) Mathematics and Natural Sciences learning motivation has a positive and significant effect on Mathematics and Natural Sciences learning achievement of the 11th grade students of Mathematics and Natural Sciences in SMA Negeri 1 Karangdowo, Klaten Regency, so that the research hypothesis is accepted. (4) Discipline of learning had a positive and significant effect on the learning achievement of MIPA students of XI MIPA grade students in SMA Negeri Karangdowo Klaten Regency. (5) Mathematics learning motivation is the most influential variable on the learning achievement of Mathematics and Natural Sciences students of class XI MIPA in SMA Negeri 1 Karangdowo, Klaten Regency.